2010
DOI: 10.1016/j.childyouth.2010.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Social capital, savings, and educational performance of orphaned adolescents in Sub-Saharan Africa

Abstract: We examine the impact of social capital on savings and educational performance of orphaned adolescents participating in a family-level economic strengthening program in Uganda. Findings indicate that if given the opportunity, poor families in Uganda will use financial institutions to save for the education of their adolescent youth. Moreover, although the results are mixed, overall, adolescents with higher levels of social capital and social support, including participation in youth groups, are likely to repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 40 publications
1
46
0
1
Order By: Relevance
“…Four studies were carried out in South Africa [60,61,63,64], one study was carried out in India [57], Honduras [58], Egypt [59] and Uganda [65][66][67][68]. All eight studies were published between 2006 and 2010.…”
Section: Community-based Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies were carried out in South Africa [60,61,63,64], one study was carried out in India [57], Honduras [58], Egypt [59] and Uganda [65][66][67][68]. All eight studies were published between 2006 and 2010.…”
Section: Community-based Interventionsmentioning
confidence: 99%
“…Two studies evaluated the Intervention with Microfinance for AIDS and Gender Equity (IMAGE), a poverty-focused microfinance initiative for women that is combined with a 12-15 month gender and HIV education curriculum [63,64]. One study examined the effects of small individual loans and mentorship on health and mental health functioning of primary school children [65][66][67][68]. Five of the seven interventions were designed for young people aged 13+.…”
Section: Community-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a low income country like Uganda, where 27.4% of population lives on $2 a day and GNI (Gross National Income) per capita is $510 (World Bank, 2014), this amount is substantial and sufficient to pay for 1.5 years of secondary education. In addition, the intervention demonstrated that along with economic benefits alleviating financial pressures from caregiving families (Ssewamala, Karimli, Han, & Ismayilova, 2010), orphaned children showed significant improvements in a range of psychosocial outcomes including educational performance (Ismayilova, Ssewamala, Mooers, Nabunya, & Sheshadri, 2012;Ssewamala & Curley, 2006;), self-esteem, depression and hopelessness (Han, Ssewamala, & Wang, 2013), and reduction in sexual risks . Although not the primary outcome, the intervention has also reduced caregiver's psychological distress (Kagotho & Ssewamala, 2012) and improved relationships between orphaned children and adults caring for them (Ismayilova, Ssewamala, & Karimli, 2012).…”
Section: Examples Of Asset-based Economic Programs For Children Withomentioning
confidence: 97%
“…At the individual level, gender (Musa, 2013;Ssewamala, Karimli, Han, & Ismayilova, 2010), place of residence (Kazeem, Jensen, & Stokes, 2010), and individual motivation (Goodman et al, 2011) have been identified as factors associated with educational outcomes among youth. At the household level, wealth status has been consistently documented as one of the factors that can influence youth educational outcomes although results have been inconclusive.…”
Section: Introductionmentioning
confidence: 99%